Hubungan Karakteristik Individu Dengan Kejadian Penyakit Antraks Tipe Kulit Pada Penduduk di Wilayah Kabupaten Bogor - Chaerul Basri (Institut Pertanian Bogor, 2009)
This research is aim to know several of risk factors about individual characteristics which are related with occurrence of skin type of anthrax disease in Bogor district for 2003-2007. The research was designed to reach out for the goal of this research is use Case Control epidemiological research design. Case of this research is taken from victim of skin type of anthrax disease record in Puskesmas Center for Health Services) and clarified as positive infected by anthrax bacterial based on laboratory serological examination in Balitvet Bogor. Control is taken from inhabitant in Bogor district which are live in the same area with people who is diagnose as a victim of skin type of anthrax disease and do not showed clinical signs of skin type of anthrax disease. Data collection is done through by structured interview and observation which is doing by researcher itself and assisted by Puskesmas staff in Bogor district. Analysis data is done trough two steps that are univariate for analysis of frequency distribution and bivariate with Chi-square. All analysis processed by SPSS 13.0. The risk factors about individual characteristics which are related with occurrence of skin type of anthrax disease is working as a farmer with OR=3.011 95% C=1.410-6.427).",